Merits of harmonic scalpel over conventional hemostasis in open thyroid surgery: a randomised controlled trial - Bajaj, Anushree; Paike, Bhalchandra; Sheikh, Shahnaz; Vaze, Vikrant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The pioneers of thyroid surgery, Theodor Kocher and Theodor Billroth, developed an acceptable technique of standardized thyroid surgery between 1873 and 1883. The aim of this prospective randomized trial was to evaluate the efficacy and safety of harmonic scalpel use compared with conventional haemostasis in open thyroid surgery. Methods: A total of 60 consecutive patients underwent open total thyroidectomy were randomized into two groups. Group A with harmonic scalpel and Group B with electrocautery with 30 patients each. Factors including age, sex, pathology, thyroid volume, haemostatic technique, operative time, drainage volume, thyroid weight, postoperative pain, postoperative complications and hospital stay. The results were analysed using the students t-test and x2. Results: No significant difference was found between the two groups concerning mean thyroid weight and mean hospital stay. The mean operative time was shorter in the harmonic scalpel group. The total fluid drainage fluid volume was lower in Harmonic scalpel group shorter in. Harmonic scalpel group experienced significantly less post-operative pain at 24 and 48 hours. Conclusions: In patients undergoing thyroidectomy, harmonic scalpel is a reliable and safe tool. AS compared with conventional haemostasis techniques, its use reduces operative times, post-operative pain, drainage volume and transient hypocalcemia.